Ranking of source-based congestion control approaches for high speed networks using AHP. (2016) - Kushwaha, Vandana; ,
Congestion control is a challenging issue in global internet because of its complex characteristics. Network congestion control can be characterised by several criteria like causes of congestion, type of congestion symptoms, congestion control location and objectives while congestion control. Thus, network congestion control can be treated as multi criteria decision-making problem. Analytical hierarchy process (AHP) is one of the ways to solve the multi criteria decision-making problem. In this paper, an attempt has been made to compute ranking of source-based congestion control approaches for high speed network using AHP model. The computed ranking will help to propose a decision-making model for congestion control algorithm and facilitate to select appropriate congestion control approach for a particular network environment.